Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

Multi-level biomarker responses in Eisenia fetida co-exposed to PE-MPs and DiBP: An ecological risk assessment based on physiological, biochemical, and molecular indicators - Yanan Zhang; Yumu Luo; Zhensi Meng; Jun Luo; Ke Li; Yuhang Lin; Minle Li; Rongren Bin; Mingming Fu; Ming Hung Wong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

PSO-ACO metaheuristic ship-UAV collaborative scheduling for maritime emergency response under marine uncertainty - Godfred Ziedor; Bin Duo; Obed Tettey Nartey; Tong Liu; Jie Lin; Junsong Luo (Ocean Engineering, 2026)

Effect of temperature on the performance of electrochemical oxygen pump in liquid lead–bismuth eutectic - Min Zhang; Wenyi Ding; Zhizhong Jiang; Lin Luo; Mingjie Zheng; Yang Li; Wangli Huang; Bin Wu; Xin Wu; Xingming Yang (Annals of Nuclear Energy, 2026)

Unveiling precursor-derived PFAS burdens in landfill leachate: TOP assay reveals ultrashort-chain PFAS and DTRO removal limitations across 11 Chinese cities - Ying Zhang; Nemin Luo; Bin Yan; Lei Wang; Haolong Zhang; Mingyuan Lin; Ting Fang; Zhenchang Zhong; Huiyan Cheng; Yan Lin (Journal of Environmental Sciences, 2026)

Exploring gut microbiota responses to low-dose thallium exposure via food chain transfer: insights from soil–plant–human systems - Lu-Xiu Lin; Wei-Jun Chen; Shun-Xing Li; Feng-Ying Zheng; Xu-Guang Huang; Feng-Jiao Liu; Jia-Yi Luo; Zhao-Jing Huang; Wen-Jie Zhang; You-Bin Zhuo; Xin Long (Environmental Geochemistry and Health, 2026)

Pasteurella multocida toxin induces apoptosis of respiratory epithelial cells by activating the PERK–NF-κB-DR5 signaling axis - Fei Wang; Yuhao Lei; Menghan Chen; Haixin Bi; Yayuan Luo; Fangfang Bai; Lin Hua; Huanchun Chen; Qigai He; Bin Wu; Zhong Peng (Veterinary Microbiology, 2026)

Corrigendum to “Busulfan plus cyclophosphamide induced spermatogenic dysfunction and recovery: A dynamic change perspective” [Toxicol. Lett. 417(2026) 111833] - Tianyu Li; Zhichen Tang; Yaping Song; Min Su; Xiao Liu; Fuping Li; Xing Wei; Xiaolei Luo; Bin Zhou; Yanyun Wang; Lin Zhang (Toxicology Letters, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

QSAR-enhanced machine learning for mechanistic insights and real-time prediction of DBPs in drinking water distribution systems - Dai-Xu Zhang; Tian-Yang Zhang; Zhen-Ning Luo; Zhu Peng; Zheng-Xiong Zheng; Yun-Qiao Zeng; Qi Fu; Ling Hu; Bing Geng; Chao-Yi Tong; Yu-Lin Tang; Bin Xu (Water Research, 2026)

Busulfan plus cyclophosphamide induced spermatogenic dysfunction and recovery: A dynamic change perspective - Tianyu Li; Zhichen Tang; Yaping Song; Min Su; Xiao Liu; Fuping Li; Xing Wei; Xiaolei Luo; Bin Zhou; Yanyun Wang; Lin Zhang (Toxicology Letters, 2026)

Sous vide processing: Influence on the binding capacity of Litopenaeus vannamei myofibrillar protein to two flavor compounds (succinic acid and 1-octen-3-Ol) - Jie Feng; Yi Luo; Ying Su; Chuandong Fang; Jiancong Huo; Shucheng Liu; Huimin Lin; Soottawat Benjakul; Bin Zhang (Food Chemistry, 2026)

Magnetic properties driving nitrogen removal improvement in magnetite-enhanced activated sludge: Mechanistic insights and process validation - Jun Shi; Luo-Kai Li; Li-Han Lin; Duo-Kun Li; Jian Lu; Sali Mustafa Saleh; Tian-Yang Zhang; Huan He; Zheng-Yu Dong; Qian Xiao; Bin Xu; Chao Zeng (Environmental Research, 2026)

Complex variable solution for multi-step shallow tunnel excavation considering gravitational effects - Luo-bin Lin; Fu-quan Chen; Chang-jie Zheng; Shang-shun Lin (Tunnelling and Underground Space Technology, 2026)

Ultrasensitive electrochemiluminescence aptasensor for heparin-binding protein based on hybridization chain reaction (HCR) amplification and magnetic enrichment - Mengxin Cheng; Wanxin Xu; Yingying Cao; Yue Lin; Shenghang Zhang; Fang Luo; Bin Qiu; Zhenyu Lin (Analytica Chimica Acta, 2026)

Key factors affecting heavy metal contamination of mangrove sediments in the Zhangjiang Estuary: Implications for environmental management - Zheng Zhang; Lianzhi Zhong; Cheng Luo; Ting Fang; Lei Wang; Bin Yan; Jinpeng Wang; Xiuwen Ren; Yan Lin (Marine Pollution Bulletin, 2026)

Disentangling seasonal dynamics and transboundary transport of PAHs in a coastal monsoon city - Haolong Zhang; Zheng Zhang; Wenhui Lin; Guohui Lin; Cheng Luo; Ting Fang; Nemin Luo; Minggang Cai; Lei Wang; Bin Yan; Yan Lin (Atmospheric Research, 2026)

Perinatal maternal lead exposure induces intergenerational neurotoxicity via mitochondrial dysfunction and mediation by perturbation of thyroid function - Lin Zhang; An-Xin Lu; Ling Li; Qian Wei; Yin Lin; Jun-Xia Liu; Li Ma; Ren-Tong Chen; Bin Luo; Chong-Huai Yan (Journal of Hazardous Materials, 2025)

Effect of alkaline electrolyzed water on lipid, protein changes, and microbial diversity of frozen-stored Dosidicus gigas based on multi-omics analysis - Yi Luo; Jie Feng; Xiao Yuan; Chuan-Dong Fang; Hui-Min Lin; Soottawat Benjakul; Bin Zhang (Food Research International, 2025)

Interfacial work function engineering enables dendrite-free zinc anode and collapse-resistant cathode - Lieyuan Zhang; Bin Xie; Chao Li; Yijia Luo; Xin Tan; Yi Yang; Fengrong Yu; Jianding Li; Yu Huo; Qiaoji Zheng; Shuai Wang; Jingxin Zhao; et al. (Chemical Engineering Journal, 2025)

Nickel phthalocyanine-catalyzed ammonia detection on a TiO2 photoelectrochemical sensor with ZIF-67 enrichment for environmental water analysis - Wenru Wu; Nuoxuan Xiong; Yue Lin; Fang Luo; Cuiying Lin; Bin Qiu; Zhenyu Lin; Zhou Jiang; Jian Wang (Water Research, 2025)

Retrieving soil heavy metal concentrations using hyperspectral remote sensing images based on three-band indices at a coal mine in China - Haorui Bai; Bin Guo; Lin Pei; Bo Zhang; Pingping Luo; Tengyue Guo; Min Wu; Xiaohan Ma (Advances in Space Research, 2025)

Regulating the coordination distance of solvation structure for high-performance aqueous zinc ion batteries - Yijia Luo; Chao Li; Lieyuan Zhang; Xin Tan; Yi Yang; Bin Xie; Dandan Zhang; Haoran Lang; Xingyu Chen; Xuemei He; Qiaoji Zheng; Xinqiao Wu; et al. (Chemical Engineering Journal, 2025)

Engineered albumin host for ratiometric fluorescent indicator-displacement assay: Distinguishing testosterone from estrone and estradiol - Yuting Luo; Linhui Peng; Zhang Lin; Zhiqing Xun; Na Li; Naiyu Liu; Yalong Wang; Xinfeng Du; Tianyi Qin; Bin Liu; Mingqiang Zhu (Chemical Engineering Journal, 2025)

Multi-objective optimal Bi-level scheduling of hybrid mobile-stationary energy storage systems for flexible distribution network - Bo Yang; Guo Zhou; Shuai Zhou; Yuanweiji Hu; Bin He; Zhengxun Guo; Zhibiao Luo; Hongbiao Li; Dengke Gao; Jingbo Wang; Lin Jiang (Journal of Cleaner Production, 2025)

One-pot synthesis of highly stable CsPbBr₃@C6H7NO3S composite and its application in nitrite fluorescent sensing - Yongzhen Qiu; Yexin Zu; Yating Zhang; Yue Lin; Fang Luo; Zuquan Weng; Cuiying Lin; Jian Wang; Bin Qiu; Zhenyu Lin (Food Chemistry, 2025)

Impact of marine chlorine emissions on secondary organic aerosols in North China Plain - Zhaoqi Gao; Lin Li; Zhou Liu; Jiangshan Mu; Zhuyi Wang; Bin Luo; Jingzhu Zhang; Shuting Tang; Hongliang Zhang; Jianlin Hu; Xuan Wang; Xuehua Zhou; et al. (Environmental Pollution, 2025)

Interfacial water masking agent: Dynamic synergistic regulation of anode and cathode for ultra-long-life aqueous zinc metal batteries - Bin Xie; Chao Li; Min Li; Lieyuan Zhang; Zhaodan Fu; Yijia Luo; Gehong Su; Xin Tan; Heng Zhang; Qiaoji Zheng; Yu Huo; Jingxin Zhao; et al. (Chemical Engineering Journal, 2025)

Carbon, nitrogen, and phosphorus ecological stoichiometry in Cenchrus fungigraminus and soil under waterlogging stress - Simeng Song; Hengyu Zhou; Pingxuan Li; Lin Zhang; Dewei Su; Dan Zheng; Zhaoxiong Zhang; Zongzhi Luo; Shikui Yu; Bin Liu; Zhanxi Lin; Dongmei Lin (Plant and Soil, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Confining bismuth in oxygen-defective BiVO4 through chemical reconstruction engineering for enhanced electrocatalytic formate generation - Jiaye Zhu; Lin Luo; Cheng Lai; Bin He; Pengzuo Chen (Chemical Engineering Journal, 2025)

Seasonal variations and risk assessment of PAHs in Xiamen: Insights into the impacts of local and long-range transport sources - Zheng Zhang; Haolong Zhang; Cheng Luo; Minggang Cai; Lei Wang; Bin Yan; Yan Lin (Atmospheric Pollution Research, 2025)

Soil viruses regulate soil nutrient cycling through themselves and their effects on host functioning to impede the growth of continuously planted Casuarina equisetifolia - Yu-Hua Wang; Lei Hong; Yi Lin; Miao-En Qiu; Jian-Juan Li; Qing-Xu Zhang; Xiao-Li Jia; Yu-Lin Wang; Li-Yuan Wang; Yang-Xin Luo; Wen-Xiong Lin; Hai-Bin Wang; et al. (Applied Soil Ecology, 2025)

Dental pulp stem cells derived exosomes inhibit ferroptosis via regulating the Nrf2-keap1/GPX4 signaling pathway to ameliorate chronic kidney disease injury - Lin Luo; Jing Wang; Jie Zhao; Bin Yang; Wenzhe Ma; Jiaru Lin (Tissue and Cell, 2025)

The consequence distance of liquid ammonia release from a pipeline in complex terrain - Lin Teng; Kangkang Wang; Bin Liu; Weidong Li; Pengbo Yin; Zhenchao Li; Xin Huang; Yu Luo; Lilong Jiang (Process Safety and Environmental Protection, 2025)

Insights into algae cell inactivation by mixed chlor(am)ines in source water: Unraveling removal mechanisms, derived risks and control methods - Zhu Peng; Tian-Yang Zhang; Qi Fu; Xiang-Chi Xie; Zhen-Ning Luo; Yu-Lin Tang; Huan He; Chao Zeng; Jian Lu; Yun-Qiao Zeng; Chen-Yan Hu; Bin Xu (Journal of Environmental Chemical Engineering, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

MRI Shrimp Sign and Parietooccipital Lesion in Progressive Multifocal Leukoencephalopathy - Wen-Qian Luo; Bin Liu; Chun-Lin Yang; Ze-Yu Zhao; Guan-Qing Wang; Xiao-Li Li; Peng Zhang (The Cerebellum, 2025)

Canagliflozin reverses doxorubicin-induced cardiotoxicity via restoration of autophagic homeostasis - Jianping Luo; Mingyuan He; Changzhu Liang; Xiaoxia Huang; Yingqi Zhu; Donghong Hu; Junyu Yan; Mingjue Li; Hairuo Lin; Wangjun Liao; Jianping Bin; Ziyun Guan; et al. (Toxicology and Applied Pharmacology, 2025)

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

Fatigue behavior of square steel strut-to-gusset plate welded connections under eccentric compression: Full-scale and reduced-scale tests - Xiaoqing Xu; Hongfa Luo; Bin Wang; Yuqing Liu; Kaixiang Miao; Rui Hao; Weiwei Lin; Yuwen Zhou; Dongyang He; Md Asadujjaman (Engineering Structures, 2025)

Biomineralization-inspired functional biomaterials: From principles to practice - Haohua Hu; Yuting Lin; Bin Yang; Xiaoqing Wen; Panqin Ma; Xian Jun Loh; Zheng Luo; Zibiao Li; Yun-Long Wu (Chemical Engineering Journal, 2025)

Checklist of marine fishes in the Beibu Gulf: fish classification, resource protection, and biodiversity challenge - Zhisen Luo; Murong Yi; Xiaodong Yang; Xiao Chen; Jinxi Wang; Changping Jiang; Fengming Liu; Konglan Luo; Xiongbo He; Hung-Du Lin; Bin Kang; Yunrong Yan (Journal of Oceanology and Limnology, 2025)

Occurrence and efficient removal of PFAS from landfill leachates using on-site DTRO systems: A comprehensive analysis across 11 Chinese cities - Rushun Wang; Yan Lin; Nemin Luo; Tao Zhang; Walter Lamparter; Bin Yan; Zhengjun Dong (Waste Management, 2024)

Cinnamic acid application inhibits the browning of cold-stored taro slices by maintaining membrane function, reducing flavonoid biosynthesis and enhancing glutathione metabolism - Yukun Wang; Hong Ye; Wei Lin; Guang Wang; Tao Luo; Jinming He; Bin Wang (Postharvest Biology and Technology, 2024)

Effectiveness of composite fume suppression and deodorizing agents in improving performance and reducing emissions of rubber modified asphalt - Juan Xie; Zheyu Ding; Haochen Luo; Zhenzhen Lu; Shuaihui Li; Xucheng Zhao; Bin Huang; Jinmei Lin (Journal of Cleaner Production, 2024)

Mechanisms of radical regulation during carbamazepine degradation by UV-LED/chlorine process with different wavelengths in water - Qi Fu; Zhi Zhang; Yi-Li Lin; Tian-Yang Zhang; Yun-Lu Zhang; Renjie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Jian Lu; Zheng-Ning Luo; Chao Zeng; Huan He; et al. (Journal of Environmental Chemical Engineering, 2024)

Unlocking the potential of Cupriavidus necator H16 as a platform for bioproducts production from carbon dioxide - Yuheng Wang; Lin Cui; Lijuan Ding; Xiaoyun Su; Huiying Luo; Huoqing Huang; Yuan Wang; Bin Yao; Jie Zhang; Xiaolu Wang (World Journal of Microbiology and Biotechnology, 2024)

The adsorption behavior and mechanism of antimony in water by jarosite ball milling mixed with nano zero-valent iron - Ming-Xuan Chen; Zhi-Bin Wu; Lin Luo; Yuan Yang; Qi-Ming Mao (Journal of Environmental Chemical Engineering, 2024)

Complex variable solution on over-/under-break shallow tunnelling in gravitational geomaterial with reasonable far-field displacement - Luo-bin Lin; Fu-quan Chen; Jin-ping Zhuang (Computers and Geotechnics, 2024)

Two-step post-synthetic modification of bipydine-based sp2c-COF for stepwise gold recovery - Bin Zhu; Rengan Luo; Chunyuan Hou; Yuan Gao; Yu Zhang; Kai Wang; Lin Zhang; Jun Luo (Chemical Engineering Journal, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

A comparative study on hydrocarbon detection using cepstrum–based methods - Cong Tang; Kang Chen; Qing-Lin He; Long Wen; Qi Ran; Bin Luo; Jing-Hui Chang; Ya-Juan Xue (Journal of Applied Geophysics, 2024)

Production of novel mung bean peptides-based zinc supplement: Process optimization, chelation mechanism, and stability assessment in vitro - Liyun Zhang; Yinxia Wang; Yalin Ni; Yongqing Zhang; Yongling Liu; Bin Du; Heng Luo; Dong Lin (Food Bioscience, 2024)

Wavelength dependency and photosensitizer effects in UV-LED photodegradation of iohexol - Meng-Yuan Xu; Chao Zeng; Yi-Li Lin; Tian-Yang Zhang; Qi Fu; Heng-Xuan Zhao; Zhen-Ning Luo; Zheng-Xiong Zheng; Tong-Cheng Cao; Chen-Yan Hu; Bin Xu (Water Research, 2024)

Inhibition of PARP1 improves cardiac function after myocardial infarction via up-regulated NLRC5 - Jia-Ming Luo; Hong-Bin Lin; Ya-Qian Weng; Ying-Hui Lin; Lu-Ying Lai; Ji Li; Feng-Xian Li; Shi-Yuan Xu; Hong-Fei Zhang; Wei Zhao (Chemico-Biological Interactions, 2024)

Highly-sensitive, broad-range, and highly-dynamic MXene pressure sensors with multi-level nano-microstructures for healthcare and soft robots applications - Boqing Jia; Zhikang Li; Tengfei Zheng; Jiaxiang Wang; Zhi-Jun Zhao; Libo Zhao; Bin Wang; Jijian Lu; Kang Zhao; Guoxi Luo; Min Li; Qijing Lin; et al. (Chemical Engineering Journal, 2024)

Enriched Environment Inhibits Neurotoxic Reactive Astrocytes via JAK2-STAT3 to Promote Glutamatergic Synaptogenesis and Cognitive Improvement in Chronic Cerebral Hypoperfusion Rats - Bin Fan; Junbin Lin; Qihang Luo; Weijing Liao; Chizi Hao (Neurotoxicity Research, 2024)

A new complex variable solution on noncircular shallow tunnelling with reasonable far-field displacement - Luo-bin Lin; Fu-quan Chen; Shang-shun Lin (Computers and Geotechnics, 2024)

Highly sensitive biosensor for specific miRNA detection based on cascade signal amplification and magnetic electrochemiluminescence nanoparticles - Jiawen Li; Cheng Chen; Fang Luo; Zhenyu Lin; Jian Wang; Aiwen Huang; Ying Sun; Bin Qiu (Analytica Chimica Acta, 2024)

Mixed chlorine/chloramines in disinfected water and drinking water distribution systems (DWDSs): A critical review - Renjie Pan; Tian-Yang Zhang; Huan He; Zheng-Xiong Zheng; Zheng-Yu Dong; Heng-Xuan Zhao; Meng-Yuan Xu; Zhen-Ning Luo; Chen-Yan Hu; Yu-Lin Tang; Mohamed Gamal El-Din; Bin Xu (Water Research, 2023)

Organophosphate diesters (DAPs) and hydroxylated organophosphate flame retardants (HO-OPFRs) as biomarkers of OPFR contamination in a typical freshwater food chain - Yin-E Liu; Xiao-Jun Luo; Hong-Chang Ding; Lin Qi; Bin Tang; Bi-Xian Mai; Giulia Poma; Adrian Covaci (Chemosphere, 2023)

A pruned feed-forward neural network (pruned-FNN) approach to measure air pollution exposure - Xi Gong; Lin Liu; Yanhong Huang; Bin Zou; Yeran Sun; Li Luo; Yan Lin (Environmental Monitoring and Assessment, 2023)

Oxygen-induced dual-signal point-of-care testing aptasensor for aflatoxin B1 detection using platinum nanoparticle catalysis in visual fluorometry and gravimetry - Fang Luo; Linxiu Zhan; Ye Deng; Kun Qiao; Nan Pan; Zuquan Weng; Cuiying Lin; Bin Qiu; Zhenyu Lin (Analytica Chimica Acta, 2023)

Impact of heat on all-cause and cause-specific mortality: A multi-city study in Texas - Chunyu Guo; Kevin Lanza; Dongying Li; Yuyu Zhou; Kristin Aunan; Becky P.Y. Loo; Jason Kai Wei Lee; Bin Luo; Xiaoli Duan; Wangjian Zhang; Zhengjun Zhang; Shao Lin; et al. (Environmental Research, 2023)

Evaluating the performance of a novel ventilated embankment structure in warm permafrost regions by numerical simulation - Zhanyuan Zhu; Zonghang He; Fei Luo; Bin Luo; Chenxuan Tang; Zuyin Zou; Zihong Guo; Weimin Xiao; Xiangang Jiang; Lin Li (Cold Regions Science and Technology, 2023)

Donor-acceptor engineered g-C3N4 enabling peroxymonosulfate photocatalytic conversion to 1O2 with nearly 100% selectivity - Zonglin Weng; Yuanfang Lin; Bin Han; Xinfei Zhang; Qin Guo; Yu Luo; Xinwen Ou; Yang Zhou; Jin Jiang (Journal of Hazardous Materials, 2023)

Rational design of donor-acceptor engineered g-C3N4 for boosted H2O2 production via photocatalytic O2 reduction - Yu Luo; Yuanfang Lin; Zonglin Weng; Bin Han; Yang Zhou; Xinwen Ou; Jin Jiang (Journal of Environmental Chemical Engineering, 2023)

Whole-genome sequencing reveals putative underlying mechanisms of biocontrol capability of IBFCBF-5 - Chen Luo; Ai-rong Shen; Ye-song Ren; Yang Zhai; Yi Cheng; Jianping Xu; Lin Wei; Ji-lie Li; Liang-bin Zeng (Acta Physiologiae Plantarum, 2023)

Performance and application of a novel drainage anti-slide pile on accumulation landslide with a chair-like deposit-bedrock interface in the Three Gorges Reservoir area, China - Shi-lin Luo; Da Huang; Jian-bing Peng; Ailifeila Aierken; Zhao Li; Xi-bin Kuang; Roberto Tomás (Computers and Geotechnics, 2023)

Low-crystalline Ni(OH)2 ultrathin nanosheets upcycled from solid wastes for efficient photoconversion of low-concentration CO2 - Bin Han; Yuanfang Lin; Yu Luo; Weizhen Liu; Xueming Liu; Zonglin Weng; Xinwen Ou; Zhang Lin (Chemical Engineering Journal, 2023)

Water quality criteria derivation and tiered ecological risk evaluation of antifouling biocides in marine environment - Hai-Wei Luo; Min Lin; Xin-Xin Bai; Bin Xu; Minjie Li; Jin-Jian Ding; Wen-Jun Hong; Liang-Hong Guo (Marine Pollution Bulletin, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Bile acids and their receptors in regulation of gut health and diseases - Sen Lin; Sutian Wang; Peng Wang; Cuiming Tang; Zhenjiang Wang; Lian Chen; Guoqing Luo; Hong Chen; Yuntao Liu; Bin Feng; De Wu; Douglas G. Burrin; et al. (Progress in Lipid Research, 2023)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

CREB1 contributes colorectal cancer cell plasticity by regulating lncRNA CCAT1 and NF-κB pathways - Bin Li; Lisi Zheng; Jiayi Ye; Chenmin Zhang; Jie Zhou; Qiaojuan Huang; Yanhua Guo; Luqin Wang; Peng Yu; Shurong Liu; Qiao Lin; Yuxia Luo; et al. (Science China Life Sciences, 2022)

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

Isolation and structural elucidation of a low-molecular-weight polysaccharide from the roots of Panax ginseng C. A. Meyer - Bin Zhao; Xin-Ying Wang; Wen Luo; Yue Lin; Chong-Ning Lv; Jin-Cai Lu (Natural Product Research, 2022)

Dynamic analysis of impulse waves generated by the collapse of granular pillars - Bo-lin Huang; Bin Li; Jia-hao Zheng; Wang-li Feng; Xiao-ting Chen; Chao-lin Luo (Journal of Mountain Science, 2022)

Geochemical characteristics and genesis of deep marine carbonate natural gas in China - Jianglong Shi; Jian Li; Jin Li; Aisheng Hao; Zhongsheng Shi; Bin Zhang; Bin Hao; Xuening Qi; Bintao Chen; Luo Xue; Lun Ma; Lei Wang; et al. (Carbonates and Evaporites, 2021)

Cytotoxicity of polyketides and steroids isolated from the sponge-associated fungus Penicillium citrinum SCSIO 41017 - Limbadri Salendra; Xiuping Lin; Weihao Chen; Xiaoyan Pang; Xiaowei Luo; Jieyi Long; Shengrong Liao; Junfeng Wang; Xuefeng Zhou; Yonghong Liu; Bin Yang (Natural Product Research, 2021)

Initial chest CT findings in COVID-19: correlation with clinical features - Zhu-jing Shen; Nan Lu; Lu-lu Gao; Jian Lv; Hua-fu Luo; Ji-feng Jiang; Chao Xu; Shi-ya Li; Ju-jiang Mao; Kai Li; Xiao-pei Xu; Bin Lin (Journal of Zhejiang University-SCIENCE B, 2020)

MiR-615 Regulates NSC Differentiation In Vitro and Contributes to Spinal Cord Injury Repair by Targeting LINGO-1 - Hongfu Wu; Lu Ding; Yuhui Wang; Tang-Bin Zou; Tao Wang; Wenjin Fu; Yong Lin; Xiaomin Zhang; Kangzhen Chen; Yutian Lei; Caitang Zhong; Chuanming Luo (Molecular Neurobiology, 2020)

Multiple genetic factors affecting the pharmacokinetic and pharmacodynamic processes of tacrolimus in Chinese myasthenia gravis patients - Huan-Yu Meng; Xi Li; Wan-Lin Jin; Cheng-Kai Yan; Xiao-Hua Dong; Qiu Xu; Yu-Yao Peng; Zhi-Bin Li; Yi Li; Zhao-Hui Luo; Li-Qun Xu; Huan Yang (European Journal of Clinical Pharmacology, 2020)

Variation of rill cross-sections with gravel and aggregating soil in the Dry-Hot Valley (SW China) - Nana Wang; Lin Ding; Gangcai Liu; Qingchun Deng; Hui Liu; Jie Wang; Wei Lv; Jun Luo; Ziyin Du; Bin Zhang (Modeling Earth Systems and Environment, 2019)

A new triterpene diglycoside from the roots of Bupleurum chinense DC. and its inhibitory effect on adipogensis in 3T3-L1 cells - Yujing Feng; Zhou-Wei Wu; Yanyan Luo; Liang Chen; Yufeng Cao; Lun Wang; Aftab Yaseen; Bin Chen; Ashfaq Ahmad Khan; Ming-Kui Wang; Guo-Lin Zhang; Xin-Feng Wang; et al. (Medicinal Chemistry Research, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile - Xue-Ming Zhou; Bin Zhang; Guang-Ying Chen; Chang-Ri Han; Kun-Chi Jiang; Ming-Yue Luo; Bo-Zheng Meng; Wen-Xin Li; Shi-Dai Lin (Natural Product Research, 2018)

Three new polyketides from the marine sponge-derived fungus Trichoderma sp. SCSIO41004 - Xiaoyan Pang; Xiuping Lin; Yongqi Tian; Rui Liang; Junfeng Wang; Bin Yang; Xuefeng Zhou; Kumaravel Kaliyaperumal; Xiaowei Luo; Zhengchao Tu; Yonghong Liu (Natural Product Research, 2018)

Increased Src Family Kinase Activity Disrupts Excitatory Synaptic Transmission and Impairs Remote Fear Memory in Forebrain Shp2-Deficient Mice - Xunyi Yan; Bin Zhang; Wen Lu; Lin Peng; Qian Yang; Wei Cao; Shen Lin; Wenyue Yu; Xiaoming Li; Yuehai Ke; Shengtian Li; Wei Yang; et al. (Molecular Neurobiology, 2017)

Antituberculosis compounds from a deep-sea-derived fungus Aspergillus sp. SCSIO Ind09F01 - Xiaowei Luo; Xuefeng Zhou; Xiuping Lin; Xiaochu Qin; Tianyu Zhang; Junfeng Wang; Zhengchao Tu; Bin Yang; Shengrong Liao; Yongqi Tian; Xiaoyan Pang; Kumaravel Kaliyaperumal; et al. (Natural Product Research, 2017)

Branched polymeric prodrug/programmed cell death 4 complexes for combinational cancer therapy - Yu-Jing He; Lei Xing; Peng-Fei Cui; Jia-Liang Zhang; Jian-Bin Qiao; Cheng-Qiong Luo; Ge Jiang; Hu-Lin Jiang (Journal of Pharmaceutical Investigation, 2017)

Rice false smut fungus hijacks the rice nutrients supply by blocking and mimicking the fertilization of rice ovary - Jie‐Hui Song; Wei Wei; Bo Lv; Yang Lin; Wei‐Xiao Yin; You‐Liang Peng; Guido Schnabel; Jun‐Bin Huang; Dao‐Hong Jiang; Chao‐Xi Luo (Environmental Microbiology, 2016)
Summary Rice false smut disease is an increasing threat to rice production in the world. Despite of best efforts, research for the infection of the fungus has yielded equivocal and conflicting results about where and how the infection is initiated and developed. Here we show a stepwise infection pattern and sophisticated regulation during this process. Initial infection occurred on the filaments, which prevented the production of mature pollen thus blocked the pollination. In the following days, the pathogen invaded the stigmas and styles, occasionally the ovaries. Expression analysis indicated that the fungus mimicked a successful fertilization process and enabled the continuous supply of nutrients for fungus to produce false smut balls. The stepwise infection of flower organs and mimicry of ovary fertilization unveiled in this study guided the rice plant into supplying nutrients for false smut ball development and represents a new and unique biological process of host pathogen interactions.

Ecological species groups and interspecific association of vegetation in natural recovery process at Xiejiadian landslide after 2008 Wenchuan earthquake - Qing-wei Yang; Shou-jiang Liu; Cui-hua Hu; Ye-bin Lin; Bin Zhang; Ming-liang Luo; Hui-ling Peng (Journal of Mountain Science, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Clinical validation of a novel real-time human papillomavirus assay for simultaneous detection of 14 high-risk HPV type and genotyping HPV type 16 and 18 in China - Hui Yang; Lie-Jun Li; Long-Xu Xie; Zhao-Yun Luo; Min Lu; Min Lin; Xiang-bin Zheng; Yue Huang; Li-Ye Yang (Archives of Virology, 2016)

Inhibition of myosin light chain kinase reduces NADPH oxidase-mediated oxidative injury in rat brain following cerebral ischemia/reperfusion - Hong-Feng Zhang; Ting-Bo Li; Bin Liu; Zheng Lou; Jie-Jie Zhang; Jing-Jie Peng; Xiao-Jie Zhang; Qi-Lin Ma; Jun Peng; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Microstructural White Matter Abnormalities and Cognitive Dysfunction in Subcortical Ischemic Vascular Disease: an Atlas-Based Diffusion Tensor Analysis Study - Lin Lin; Yunjing Xue; Qing Duan; Bin Sun; Hailong Lin; Xiaodan Chen; Ling Luo; Xiaofan Wei; Zhongping Zhang (Journal of Molecular Neuroscience, 2015)

Oculopharyngeal Muscular Dystrophy: Phenotypic and Genotypic Studies in a Chinese Population - Jingli Shan; Bin Chen; Pengfei Lin; Duoling Li; Yuebei Luo; Kunqian Ji; Jinfan Zheng; Yun Yuan; Chuanzhu Yan (NeuroMolecular Medicine, 2014)

Protective effect of vitexin compound B-1 against hypoxia/reoxygenation-induced injury in differentiated PC12 cells via NADPH oxidase inhibition - Zhong-Bao Yang; Bin Tan; Ting-Bo Li; Zheng Lou; Jun-Lin Jiang; Ying-Jun Zhou; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

HIRA is essential for the development of gibel carp - Meng-Yu Wang; Qiu-Hong Guo; Xin-Zheng Du; Li Zhou; Qian Luo; Qiao-Hui Zeng; Jia-Lin Wang; Hao-Bin Zhao; Yu-Feng Wang (Fish Physiology and Biochemistry, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Soil microbial communities and enzyme activities in a reclaimed coastal soil chronosequence under rice–barley cropping - Qinglin Fu; Chen Liu; Nengfei Ding; Yicheng Lin; Bin Guo; Jiafa Luo; Hailong Wang (Journal of Soils and Sediments, 2012)

Collateral vessel growth induced by femoral artery ligature is impaired by denervation - Ming-ying Luo; Bao-lin Yang; Feng Ye; Xiaoqiong Wu; Song Peng; Bin Yi; Wei Wang; Wu Zhu; Hua Luo; Jian-Guo Wen; Wei-Jun Cai; Jutta Schaper; et al. (Molecular and Cellular Biochemistry, 2011)

Effect of Dietary Supplementation with Copper Sulfate or Tribasic Copper Chloride on the Growth Performance, Liver Copper Concentrations of Broilers Fed in Floor Pens, and Stabilities of Vitamin E and Phytase in Feeds - Lin Lu; Run L. Wang; Zheng J. Zhang; Fred A. Steward; Xugang Luo; Bin Liu (Biological Trace Element Research, 2010)

Angiotensin IV elevates oxytocin levels in the rat amygdala and produces anxiolytic-like activity through subsequent oxytocin receptor activation - Chad E. Beyer; Jason M. Dwyer; Brian J. Platt; Sarah Neal; Bin Luo; Huai-Ping Ling; Qian Lin; Robert J. Mark; Sharon Rosenzweig-Lipson; Lee E. Schechter (Psychopharmacology, 2010)

Characterization of Burkholderia cepacia complex from cystic fibrosis patients in China and their chitosan susceptibility - Yuan Fang; Miao-miao Lou; Bin Li; Guan-Lin Xie; Fang Wang; Li-Xin Zhang; Yuan-Chan Luo (World Journal of Microbiology and Biotechnology, 2010)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)